(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
We attempt to present and explain the distinctio formalis ex-nature rei. a notion that many experts have regarded as fundamental in Duns Scoto´s philosophy, since this would signal an important novelty related Aristotelian and Thomistic types of distinctions, at the time a new metaphysics and an original approach of the cognitive act would emerge. Likewise, we will try to show how the formal distinction would be assimilated to the esse intelligibille or esse obiectivum, thus opening an intermediate area between the real and the intelligible thing which we can name objective.